Usaha Pengembangan Pengungkapan Masalah Lingkungan Pada Laporan Tahunan - Abdul Rohman (Universitas Muhammadiyah Yogyakarta, Indonesia, 2002)
The accounting profession requires that financial statements reveal all information that may affect the user's decision-making. Along with this it is necessary to attempt to accommodate the needs of the parties who have an interest in a business entity to information regarding environmental issues. For that environmental information should be included in the annual report. Environmental accounting at the moment is still a theme of debate. This article will try to discuss environmental issues with some emphasis: methods of valuation, disclosure, reporting and quality of disclosure of environmental issues in the context of the annual report.